Chatbot dalam Deteksi Kesehatan Mental : Tinjauan Literatur - Dewi, Bunga Nur Indah; Achmad, Maulana; Assyfa, Nurul; Sanggara, Renalda Dhava; Julliyana, Ressa; Farhan, Satria Rifqi; Sukaesih, Nunung Siti (Universitas Nurul Jadid, 2025)
Background: The development of Artificial Intelligence (AI) technology in the healthcare sector has advanced rapidly and made a significant contribution to the progress of human civilization. Mental health is a fundamental aspect that affects the well-being of individuals and society as a whole. However, in reality, access to mental health services remains a major challenge in many regions worldwide, including Indonesia. Methods:This study employs a scoping review method to identify and map existing literature on innovations and the impact of AI-powered chatbots in the context of mental health detection.The article search process was carried out using electronic databases such as google schoolar and PUBMED. Then the articles that have been obtained are selected again by looking at the title, abstract and also the inclusion and exclusion criteria and obtained articles that are suitable for further review. Results: Searches across several journal databases found seven journal articles that met the criteria: articles focusing on the benefits of AI in detecting mental health issues, published in 2020, full-text, and written in English.The seven studies analyzed showed a decrease in depression and anxiety symptoms in people who consulted online regarding their mental health problems. Conclusion: In addressing mental health issues, chatbots can be used as a tool for mass screening to reduce symptoms of depression and anxiety while providing easy access to mental health support without stigma. However, chatbots have limitations in deep clinical assessment, lack critical thinking and dynamic adaptation, and pose risks of misdiagnosis in complex cases. Therefore, chatbots can serve as